Torts and other wrongs - Gardner, John, 1965-2019 (Oxford : Oxford University Press, 2020)
This text collects John Gardner's celebrated essays on the theory of private law, alongside two new essays. Together they range across the central puzzles in understanding the significance of outcomes, the role of justice in private law, strict liability, the reasonable person standard, and the role of public policy in tort law.
This edition previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 17, 2020).
Keywords: Torts; Law; Laws of specific jurisdictions & specific areas of law